Unveiling the Hall effect and electrical transport properties of chlorophyll–polypyrrole films deposited on ITO substrate for optoelectronic applications - Yoon, Yap Lai; Sheng, Chan Kok (Elsevier, 2026)
This work presents, for the first time, the comprehensive characterization of the electrical properties and Hall effect response of a chlorophyll–polypyrrole composite thin film deposited on an ITO substrate. A markedly higher conductivity is achieved for the composite thin film compared with the pure ITO substrate, which demonstrates the significant role of the chlorophyll–polypyrrole matrix in enhancing charge carrier transport. The conductivity is observed to decrease systematically with increasing thickness of the deposited layer, a trend commonly attributed to enhanced scattering, increased defect density, and reduced carrier mobility in thicker films. The current–voltage (I–V) characteristic curve exhibits a linear electrical response, reflecting the intrinsic ohmic nature of the charge transport within the film, and thereby highlighting the strong potential of this hybrid material as a candidate for capacitor-based solar energy storage as well as for integration into optoelectronic devices. Moreover, both the Hall voltage and the charge carrier density exhibit a pronounced dependence on the applied magnetics flux density, underlining the sensitivity of the composite to external electromagnetic perturbations. Finally, the consistently observed negative polarity of the Hall voltage provides unambiguous evidence for electrons being the dominant charge carriers, thereby confirming the n-type semiconducting behavior of the composite thin film